2009
DOI: 10.1111/j.1365-2354.2008.00993.x
|View full text |Cite
|
Sign up to set email alerts
|

The concept of confidence - the nurse's perception

Abstract: The purpose of this paper is to investigate a nurse's understanding of the concept of confidence and what a nurse thinks affects the experience of confidence in the patient relationship. The project has a hermeneutic design using a research interview method. Nine nurses were interviewed. A hermeneutic approach was used in the analysis of the data. Interpretation of the data was linked to Segesten's model for confidence. Analysis of the data generated two major themes in relationship to the comprehension a nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 13 publications
1
13
0
1
Order By: Relevance
“…). Nevertheless, it is important to understand this attribute, because confidence levels will affect nurses’ performance (Leigh ; Perry ) and patients’ feelings of security (Haavardsholm & Naden ). In addition, the evidence has shown that there were significant relationships between nurses’ knowledge and attitudes in other aspects, such as attitudes towards older people (Liu et al .…”
Section: Introductionmentioning
confidence: 99%
“…). Nevertheless, it is important to understand this attribute, because confidence levels will affect nurses’ performance (Leigh ; Perry ) and patients’ feelings of security (Haavardsholm & Naden ). In addition, the evidence has shown that there were significant relationships between nurses’ knowledge and attitudes in other aspects, such as attitudes towards older people (Liu et al .…”
Section: Introductionmentioning
confidence: 99%
“…They were allowed to try, fail and experiment, and with guidance from the teachers, their perception of pressure in learning was reduced. Results from Haavardsholm and Nåden's () study confirmed that feeling confident and secure is essential for nurses in their relationships with patients. The students described feeling ‘secure’ as feeling safe from danger and found that they learn more when they feel safe.…”
Section: Discussionmentioning
confidence: 85%
“…Experienced nurses tend to have greater confidence in their ability despite not actually demonstrating a higher level of ability than less experienced staff (O'Shea, 1999). Within the literature, confidence has been described as a combination of feeling relaxed with one's role and understanding the significance of the activities which comprise clinical practice (Haavardsholm andNaden, 2009, Smith, 2012). Rowe et al (1998) identified that poor mathematical skills in nurses can increase the risk of drug errors.…”
Section: Discussionmentioning
confidence: 99%